An Attempt to Assess the Factors Determining Production Unit Flexibility - a Practical Interpretation - Nogalski, Bogdan; Niewiadomski, Przemysław (Studia Oeconomica Posnaniensia, 2017)
The main objective of the article is to develop a set of key areas - from the point of view of experts of manufacturing companies of the agricultural machinery sector - factors determining production unit flexibility, and to determine the level at which - each of the mentioned ones - the manufacturers should implement and currently implement.